Putting morphology to the test: An established classification scheme reliably stratifies salivary gland cytology by risk of malignancy with substantial interobserver agreement. Issue 4 (2nd November 2020) - Lubin, Daniel J.; Griffith, Christopher C.; Buonocore, Darren J.; Wei, Xiao‐Jun; Lin, Oscar
Abstract : Background: The Milan System for Reporting Salivary Gland Cytopathology describes several salivary gland fine‐needle aspiration cytology (SGFNAC) morphologies developed by Griffith et al. Basaloid neoplasms are pleomorphic (PB) or monomorphic with fibrillary (MBFib), hyaline (MBHy), or other (MBOther) matrix. Oncocytoid neoplasms can be pleomorphic (PO), demonstrate granular and/or vacuolated cytoplasm (OGV), or be monomorphic with mucinous (MOMuc), cystic (MOCyst), or other (MOOther) background. In the current study, the authors explore interobserver agreement (IOA) and risk of malignancy (ROM) for these subcategories. Methods: The study included 169 SGFNAC cases with surgical follow‐up. Four reviewers categorized these cases using the criteria of Griffith et al. with consensus determined by majority. For all morphologic categories, IOA (using the Fleiss kappa) and ROM were calculated. Results: ROMs for basaloid categories were: PB: 100% (1 of 1 case); MBHy: 71.4% (5 of 7 cases); MBFib: 50.0% (3 of 6 cases); and MBOther: 47.4% (9 of 19 cases). ROMs for oncocytoid neoplasms were: OGV: 100% (10 of 10 cases); MOMuc: 92.3% (12 of 13 cases); PO: 88.9% (8 of 9 cases); MOOther: 33.3% (5 of 15 cases); and MOCyst: 0 (0 of 1 case). The system demonstrated substantial agreement overall (κ = 0.69). For basaloid neoplasms, the IOA results were: MBHy: κ = 0.59; MBFib: κ = 0.41; MBOther: κ = 0.41; and PB: κ = 0.11. For oncocytoid neoplasms, the IOA results were: MOMuc: κ = 0.88; OGV: κ = 0.67; PO: κ = 0.63; MOOther: κ = 0.57; and MOCyst: κ = 0.18. Conclusions: The SGFNAC scheme proposed by Griffith et al. and incorporated into the Milan System for Reporting Salivary Gland Cytopathology demonstrated substantial agreement overall, with particularly high agreement for the MOMuc, OGV, PO, and MBHy categories. The PB and MOCyst categories demonstrated slight agreement and may be improved by revised criteria. The PB, PO, MOMuc, and OGV categories demonstrated high ROM, and the latter 2 categories might best be classified as suspicious for malignancy. Abstract : In the current study, 4 cytopathologists independently categorize 169 salivary gland cytology cases with surgical follow‐up using a scheme devised by Griffith et al. and adopted by the Milan System for Reporting Salivary Gland Cytopathology. They report substantial interobserver agreement overall and particularly strong agreement for categories such as monomorphic oncocytoid neoplasm with mucinous background, oncocytoid neoplasm with granular and/or vacuolated cytoplasm, pleomorphic oncocytoid neoplasm, and monomorphic basaloid neoplasm with hyaline matrix. The study also confirms a high risk of malignancy for pleomorphic basaloid neoplasms, pleomorphic oncocytoid neoplasms, monomorphic oncocytoid neoplasms with mucinous background, and oncocytoid neoplasms with granular and/or vacuolated cytoplasm, suggesting that the latter 2 entities might best be classified under Milan category V: suspicious for malignancy.